2022
DOI: 10.1503/cmaj.211416
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate use of clinical practices in Canada: a systematic review

Abstract: Background: Inappropriate health care leads to negative patient experiences, poor health outcomes and inefficient use of resources. We aimed to conduct a systematic review of inappropriately used clinical practices in Canada. Methods: We searched multiple bibliometric databases and grey literature to identify inappropriately used clinical practices in Canada between 2007 and 2021. Two team members independently screened citations, extracted data and assessed methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 168 publications
0
17
0
3
Order By: Relevance
“…In related research, Squires and colleagues provide contemporary estimates of these twin problems of underuse and overuse in Canada. 4 Using Canadian data from 174 studies published from 2007 to 2021, they found a median proportion of inappropriate care (either underuse or overuse) of 30%. This inventory of shortfalls in the delivery of effective care comes after decades of efforts to address such quality problems, 5 begging the question, “What should we be doing to deliver better quality care?”…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In related research, Squires and colleagues provide contemporary estimates of these twin problems of underuse and overuse in Canada. 4 Using Canadian data from 174 studies published from 2007 to 2021, they found a median proportion of inappropriate care (either underuse or overuse) of 30%. This inventory of shortfalls in the delivery of effective care comes after decades of efforts to address such quality problems, 5 begging the question, “What should we be doing to deliver better quality care?”…”
mentioning
confidence: 99%
“…The authors of the related systematic review 4 identified glycosylated hemoglobin (HbA 1c ) testing as the most frequently underused diagnostic test in Canada. Addressing underuse of HbA 1c testing might prompt use of the many effective therapies for diabetes that have become available in recent years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dans une recherche connexe, la D re Janet Squires et ses collègues fournissent des estimations plus récentes du problème double de sous-utilisation et de surutilisation des soins au Canada 4 . À partir de données canadiennes tirées de 174 études publiées entre 2007 et 2021, ces chercheurs concluent que la proportion médiane de soins inappropriés (sous-utilisation ou surutilisation) est de l’ordre de 30 %.…”
unclassified
“…Les auteurs de l’étude systématique dirigée par la D re Squires mentionnée ci-dessus 4 ont déterminé que l’analyse de l’hémoglobine glyquée (HbA 1c ) est le test diagnostique le plus fréquemment sous-utilisé au Canada. Aborder cet enjeu de sousutilisation pourrait mener à l’administration de nombreux traitements efficaces contre le diabète élaborés ces dernières années.…”
unclassified